E-TOURISM: AN INNOVATIVE APPROACH FOR THE HOME STAY TOURISM IN KERALA - ANUPAMA. K and KOSHY C.J (ZENITH International Journal of Multidisciplinary Research, 2014)
This paper deals with e-tourism, innovation and growth. The Internet is revolutionising the distribution of tourism information and sales. The Home stay initiative that is booming in tourist location of Kumarakom is a venture of its kind. This paper examines problems and solutions related to electronic commerce in the tourism industry and suggest recommendations for successful e-commerce strategies in tourism to be applied by the industry and the government in Kerala to promote home stay through E-tourism.